Gastrodiplomacy as Optimization of the Sustainable Tourism Sector in Pati Regency - Safitri, Desy Ayu; Rusdarti (Economic Education Analysis Journal, 2024)
The gastrodiplomacy model is an important effort to introduce, promote and develop sustainable tourism nationally and in the regions. The gastrodiplomacy model is a humanistic approach and promotion of the wealth, uniqueness and characteristics of a region, including tourist destinations, through culinary or food. The integration carried out is focused on the culinary sector while still prioritizing tourism, environmental, social and economic elements. The main problem in tourism development is the absence of an effective, efficient, sustainable, integrated and sustainable gastrodiplomacy model based on superior regional culinary delights. In fact, every tourist destination is very synonymous with the culinary sector as souvenirs/souvenirs which also serve as a medium for gastrodiplomacy for tourists. Based on these problems, the aim of this research is to analyze and conduct studies related to gastrodiplomacy in optimizing sustainable tourism in Pati Regency. The urgency of this research is that the gastrodiplomacy model is very suitable in efforts to introduce and promote local wisdom, especially in the tourism sector, to both domestic and foreign communities through culinary delights. This research uses a qualitative approach using interview techniques, observation, documentation, demonstration and Focus Group Discussion (FGD). Research stages include introduction, implementation and evaluation.